Optimization of spider web-inspired phononic crystals to achieve tailored dispersion for diverse objectives. (1st November 2021) - Dal Poggetto, Vinícius F.; Bosia, Federico; Miniaci, Marco; Pugno, Nicola M.
Graphical abstract: Highlights: Spider web-inspired phononic crystals can achieve optimized performance. One proposed design achieves maximal band gap width (48%) in the low-frequency range. A second design filters only a fundamental frequency for non-linear wave detection. Other designs create polarization band gaps (4.2 kHz range) or isolated Dirac cones. Abstract: Spider orb webs are versatile multifunctional structures with optimized mechanical properties for prey capture, but also for transmitting vibrations. The versatility of such a system mainly derives from its variable geometry, which can be effectively used to design phononic crystals, thus inhibiting wave propagation in wide frequency ranges. In this work, the design of spider web-inspired single-phase phononic crystals through selective variation of thread radii and the addition of point masses is proposed, determined through the use of optimization techniques. The obtained results show that spider web geometry displays a rich vibration spectrum, which by varying its the geometric characteristics and adding localized masses can be tailored to manipulate wave modes, and the resulting two-dimensional phononic crystals present wide complete band gaps generated by Bragg scattering and local resonances.